Patient safety with special reference to adverse events taking place in the cases discussed in mortality and morbidity meets - Mirza, Moonis; Jan, Farooq A.; Sofi, Fayaz Ahmad; Wani, Rauf Ahmad (International Journal of Research in Medical Sciences, 2016)
Background: There is an increasing belief that an institution’s ability to avoid patient harm will be realized when it creates a culture of safety among its staff members. Aims to study the cases discussed in mortality meets. Methods: Critical analysis of cases discussed in mortality and morbidity meet were done for one year by using WHO Structured questionnaire on patient safety (RF-1 & RF-2 forms) along with their record review and interview to the concerned staff. Results: 62 mortality and morbidity meetings were conducted during the study period of one year. Cardiac/ Respiratory arrest was the most common adverse event studied (67.7%) followed by unexpected death (48.4%). 52.7% of studied adverse events showed signs of healthcare team responsible for causing adverse events, mainly related to the therapeutic care (64.8%). 47% of adverse events were categorized preventable. Conclusions: Mortality and Morbidity Meets should be made mandatory in all hospitals.